(untitled) (Palíndromo, 2020)
Considering participation and social experience fundamental elements for the realization of many contemporary art works, this article brings out the voice, or the element of speech, discourse and story, as points of updating the artist-work-public tension, through the analysis of the work VOZ ALTA (2008) by the artist Rafael Lozano-Hemmer. It is the speech and listening, and their respective processes of language translation, that configure the polyphonies of this sonorous work in the face of the Latin American problematics of the limits - and also, of the powers - of saying today.